Nonverbal Communication - PE79 - 202101 - Freundt Thurne Freundt, Úrsula María (2021)
Course Overview: This course will cover various theories and research on nonverbal communication codes (e.g., kinetics, touch, voice, appearance) and social functions (e.g., impression formation and management). The course is roughly divided into three sections: channels of nonverbal communication, functions of nonverbal communication, and applied topics in nonverbal communication. By the end of the course, students are expected to understand the different channels of nonverbal communication and their various functions in human interaction.